2019
DOI: 10.3390/polym11060949
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Thermal Stability of Hydrophobic Associative Polymer Aqueous Solution Using a “Triple-Protection” Strategy

Abstract: Because of their high viscoelasticity, Hydrophobic Associative Water-Soluble Polymers (HAWSPs) have been widely used in many industrial fields, especially in oilfield flooding and fracturing. However, one major problem which limits the wide applications of HAWSPs is their weak resistance to high temperatures. Once the temperature increases over 100 °C, the viscosity of the fracturing fluid decreases rapidly, because high temperatures reduce fluid viscosity by oxidizing the polyacrylamide chains and weakening t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Finally, the aqueous saline polymer solution of (A 35 N 35 P 30 ) exhibited a transparent aspect indicating great salt tolerance and excellent thermal stability of this copolymer under harsh conditions of 150°C and 250,000 ppm of NaCl. Recently, Zhao et al reported the thermal stability of water soluble ionic terpolymers without the presence of thermo‐responsive moieties in the resultant materials 68,69 . At the beginning (0–20 min), the viscosity of terpolymer showed a decrease with the increase of temperature from 25 to 140, 160, and 200°C, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the aqueous saline polymer solution of (A 35 N 35 P 30 ) exhibited a transparent aspect indicating great salt tolerance and excellent thermal stability of this copolymer under harsh conditions of 150°C and 250,000 ppm of NaCl. Recently, Zhao et al reported the thermal stability of water soluble ionic terpolymers without the presence of thermo‐responsive moieties in the resultant materials 68,69 . At the beginning (0–20 min), the viscosity of terpolymer showed a decrease with the increase of temperature from 25 to 140, 160, and 200°C, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The conformation is mainly affected by the rigidity of the polymer and the forces between groups and molecular chains. Although rigidity of the polymer worsens the flexibility of the molecular chain, it can make the molecular chain more extended [ 32 ]. Therefore, increasing the rigidity of the polymer can effectively increase the temperature resistance, and the introduction of the hydrophobic group can also change the conformation of the polymer at high temperatures [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sarsenbekuly et al [ 54 ] observed that the viscosity of synthesized polymeric solution decreased with an increase in temperature for lower concentrations of HAPAM [ 54 ]. Likewise, Yang et al [ 57 ] noted that the addition of a lower concentration (10%) of N -vinyl-2-pyrrolidone hydrophobic moieties to a copolymer of acrylamide and acrylic acid yielded a lower viscosity of the polymer. On the other hand, when the polymer concentration is above the CAC, the viscosity of the polymer increases with temperature until it reaches a maximum point and thereafter decreases.…”
Section: Polymers Utilized For Eormentioning
confidence: 99%